2006
DOI: 10.1007/s10600-006-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of essential oil from seeds of Anethum graveolens cultivated in China

Abstract: Dill, Anethum graveolens L. (Apiaceae), is an annual plant with a strong spicy odor [1]. Dill has been known since antiquity as an agent for increasing the stomach tonus and has been used for aches in the stomach and intestines, dispepsia, bladder inflammation, liver diseases, headaches, cramps, and insomnia [2]. The essential oil (EO) of dill seeds contains biologically active compounds [3,4].We used EO from dill seeds collected in the Xinjiang-Uigur Autonomous Region of China. EO was extracted from dill seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The physiological effects of dill volatile oil were occurred by its active ingredients i.e. carvone, limonine and apiol (Yili et al, 2006). Production of medicinal and aromatic plants using bio-fertilizers became an essential process to ensure the safety, not only for human, but also for the environment in which we live.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological effects of dill volatile oil were occurred by its active ingredients i.e. carvone, limonine and apiol (Yili et al, 2006). Production of medicinal and aromatic plants using bio-fertilizers became an essential process to ensure the safety, not only for human, but also for the environment in which we live.…”
Section: Introductionmentioning
confidence: 99%
“…No analgesic effects were noted for either extract during the hot palate test. Yili et al [21] reported that Anethum graveolens has been used traditionally to alleviate headaches and to reduce stomach, intestine and bladder inflammation. A previous study, somewhat similar to the present experiment, identified the anti-inflammatory effects of dill.…”
Section: Discussionmentioning
confidence: 99%
“…Maintains Bone Health: Dill seed is also having good quality of calcium [86] of which, is an important element [86] protect from bone loss and bone mineral density reduction. Millions of people affected by osteoporosis each year and calcium, along with other essential minerals, is a key component in the proper growth and development of bones and the repair of injured bones as well.…”
Section: C)mentioning
confidence: 99%